Inhibition of microRNA‐21‐3p suppresses proliferation as well as invasion and induces apoptosis by targeting RNA‐binding protein with multiple splicing through Smad4/extra cellular signal‐regulated protein kinase signalling pathway in human colorectal cancer HCT116 cells. (16th April 2018) - Hou, Nengyi; Guo, Zhiyi; Zhao, Gaoping; Jia, Guiqing; Luo, Bin; Shen, Xiaogang; Bai, Yifeng
Summary: MicroRNA‐21‐3p (miR‐21‐3p), the passenger strand of pre‐mir‐21, has been found to be high‐expressing in various cancers and to be associated with tumour malignancy, which is proposed as a novel focus in malignant tumours. Colorectal cancer (CRC), currently known as one of the most prevalent malignancy, is a leading cause of cancer death. This study aimed to investigate the key role of miR‐21‐3p in CRC by inhibiting its expression using transfection with miR‐21‐3p inhibitors into human CRC HCT116 cells. Results showed that the expression of miR‐21‐3p was higher than other CRC cells used in the study including Lovo, HT29, Colo320 and SW480 cells, inhibition of which suppressed the proliferation and induced cell cycle arrest in HCT116 cells. Besides, transfection with miR‐21‐3p inhibitors also attenuated cell migration and invasion, and induced apoptosis as well. Moreover, luciferase assay confirmed RBPMS as a direct target of miR‐21‐3p in HCT116 cells. Further, miR‐21‐3p inhibitors increased the nuclear accumulation of Smad4 and reduced phosphorylation of ERK. Interestingly, we found that silence of RBPMS using RNA interference (siRNA) not only elevated the cell viability but also increased the phosphorylation of ERK and reversed the nuclear accumulation of Smad4 induced by miR‐21‐3p inhibitors in HCT116 cells. Data suggest that inhibition of miR‐21‐3p suppresses cell proliferation, invasion as well as migration and induces apoptosis by directly targeting RBPMS through Smad4/ERK signalling pathway in HCT116 cells. Our study demonstrates miR‐21‐3p as a potent target for suppressing tumour progression of CRC which may have implications in CRC therapy in the future.